THE MANIFESTATION OF NATIONAL AND CULTURAL PECULIARITIES IN A COMPARATIVE STUDY OF ENGLISH TRANSLATIONS OF WEDDING RITUAL FOLKLORE (Scientific journal of the Fergana State University, 2024)
The article analyzes the features of Uzbek national wedding ceremonies, the manifestation of important national cultural characteristics based on English translations of wedding folklore texts and their comparative study. Sources, scientific literature, research analysis with a comparison of translations into English and Uzbek languages are given.